Digital Technologies and Their Role During the Practice Period of Future Technology Teachers - Baimetov M.M. (American Journal Of Social Sciences And Humanity Research, 2026)
The article discusses digital technologies and their role during the internship of future technology teachers, the use of digital technologies in the educational process, and the impact of these technologies on teachers and students.